Achievements and Prospects of Treatment of Chronic Gastritis: Pencapaian dan Prospek Pengobatan Gastritis Kronis - Ochilov Alisher Kamilovich; Ochilova Gulrukh Saidovna (Academia Open, 2022)
This article presents a comprehensive examination of the influence of genetic factors on individual drug response in pharmacotherapy, emphasizing the potential for personalized medicine and minimizing the risk of adverse drug reactions. The study aims to explore the goals, methods, results, and implications of incorporating modern approaches to personalized pharmacotherapy. By understanding the role of genetics in drug response, physicians and researchers can envision improved methods of tailoring treatments to individual patients, ultimately reducing the likelihood of side effects and optimizing therapeutic outcomes. This article highlights the promising prospects of personification of pharmacotherapy, highlighting the potential for revolutionizing medical practice and enhancing patient care. Highlights: Influence of genetic factors: This article examines the significant impact of genetic factors on an individual's response to drugs in pharmacotherapy, highlighting the importance of understanding genetic variations for personalized treatment. Personalized medicine potential: The study explores the potential for personalized pharmacotherapy, aiming to tailor drug treatments based on an individual's genetic profile, with the goal of minimizing side effects and optimizing therapeutic outcomes. Enhancing patient care: By considering genetic factors, healthcare professionals can anticipate a reduction in adverse drug reactions and improve treatment effectiveness, leading to enhanced patient care and better treatment outcomes. Keywords: Genetic factors, personalized pharmacotherapy, individual drug response, side effects, treatment outcomes.